31 CEREBRAL PERFUSION IN NEONATES UNDERGOING REPAIR OF COMPLEX CONGENITAL HEART DEFECTS IS DETERMINED BY CARBON DIOXIDE PREOPERATIVELY BUT BY BLOOD PRESSURE POSTOPERATIVELY. (1st March 2006) - Henson, J.; Krajewski, K.; Edmonds, H.; Sehic, A.; Austin, E.; Mitchell, M.
Abstract : Background: Preoperative studies of neonates with congenital heart disease have demonstrated that increased pCO2 results in increased cerebral perfusion, while hyperventilation with lower levels of pCO2 results in both less cerebral perfusion and pathologic changes on MRI brain scans. However, because hyperventilation with lower levels of pCO2 is often essential immediately post-neonatal cardiac surgery in order to correct acidosis and promote hemodynamic stability, post-cardiopulmonary bypass ventilatory strategy is both critically important and highly controversial. In order to determine the optimal management strategy in infants undergoing heart surgery, we examined the relationship between mean arterial pressure (MAP), end tidal CO2 (ETCO2), peripheral oxygen saturation (SaO2 ), and left cerebral oxygen saturation (LSaO2) pre- and post-cardiopulmonary bypass in an anatomically homogeneous cohort of neonates undergoing primary complete cardiac repair. Methods: 15 neonates with interrupted aortic arch and ventricular septal defect undergoing primary complete repair at Kosair Children's Hospital were enrolled in this study. Serial simultaneous measurements of MAP, SaO2, ETCO2, and LSaO2 using near-infrared spectroscopy (NIRS Somenetics Inc.) were made at 5-minute intervals pre- and postseparation from cardiopulmonary bypass. Linear and parametric regression analysis was used to look for relationships between percent change in MAP, SaO2, ETCO2, and LSaO2 . Results: Pre-cardiopulmonary bypass, changes in cerebral saturation were related to changes in ETCO2 in a linear fashion ( R 2 = .421), while there was no observed relationship to MAP ( R 2 = .078). Post-cardiopulmonary bypass, changes in cerebral saturation were tightly related to changes in MAP ( R 2 = .357) but not to changes in ETCO2 ( R 2 = .086). No relationship existed between changes in cerebral saturation and changes in SaO2 either pre- or post-cardiopulmonary bypass. Conclusions: Consistent with theories of cerebral autoregulation, cerebral saturation pre-cardiopulmonary bypass was determined by changes in end tidal CO2 but not by changes in blood pressure or peripheral oxygenation. However, this relationship was obliterated post-cardiopulmonary bypass, where changes in blood pressure became the major determinate of changes in cerebral saturation. This dysautoregulation may be secondary to cerebral edema or injury occurring during the cardiopulmonary bypass run and suggests that immediately postoperatively a strategy of hyperventilation in order to maintain mean arterial pressure is justified.